Rancang Bangun Sistem Informasi Penjualan Ikan Cupang Berbasis Web pada Toko Eterno Betta Fish - Muhamad Aulia Mufid; Nardiono (CV. Multi Kreasi Media, 2023)
The development of information technology has grown very rapidly, and it is often heard about internet technology which is the latest development of information technology. The current technology has developed towards a user friendly which is considered to make it easier for the user or users to understand or carry out the functions of the internet. Eterno Betta Fish stores betta fish not by category and type, sellers and buyers will find it difficult to find the desired betta fish during the buying and selling process in the store. The sales process to get betta fish usually buyers go to a special store for ornamental betta fish. Due to the ongoing pandemic, many potential buyers find it difficult to buy betta fish because many shops have closed, and sales activities are limited. In addition, the seller does not record sales transactions of how many betta fish are sold each day, cannot calculate the profit from sales each day. Can only calculate the amount of money earned in the sale process that day betta fish sold every day without knowing what betta fish were sold. To provide solutions to these problems, it is necessary to have a sales information system that can facilitate sellers and buyers in conducting transactions. The development method for this system uses themethod waterfall, which has a more systematic stage. Based on the tests that have been carried out, this system can be used as needed. The result of using this sales information system is to provide convenience and efficiency for sellers and buyers in processing transactions and recording sales transactions every day.